ENGLISH MATERIALS DEVELOPMENT FOR AN UNDERGRADUATE COMMUNICATION STUDY PROGRAM: A NEED ANALYSIS IN INDONESIAN CONTEXT - Dewi, Henda Harmantia; Hidayatulloh, Sibakhul Milad Malik; Sukarno, Sukarno; Lestari, Aryanti Eka; Dewi, Ifti Luthviana; Ciptaningrum, Dyah Setyowati (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Need analysis (NA) is one of the initial steps in developing learning materials. In the English for Specific Purposes (ESP) context, it is an essential asset to identify learners’ needs and determine the areas they are lacking. Thus far, NA particularly in Communication Science Program (CSP) in Indonesia has not been widely explored. In University Y, the CSP students are lacking English language learning materials. Therefore, this mixed-method study aims to explore the results of NA for developing such materials. The data were gathered through document analysis, lecturer and alumna interviews, along with student surveys. The results revealed that students' learning needs focus on the desire to improve their English proficiency, particularly in speaking and grammar, for career orientation. Moreover, the materials should be compiled with text types that support the achievement of the goals e.g., advertisements, reports, narrative and argumentative texts that are preferable to be taught through a BL delivery method. These materials should also be actualized in activities that can accommodate three learning styles, namely visual, audio, and kinesthetic, with more emphasis on the first. The implication of these findings will be helpful to create a more effective English class based on the current demands.